Diversity of apoidea and diptera in UiTM Pahang / Nur Thabitah Shaikh Nasir ... [et al.] - Shaikh Nasir, Nur Thabitah; Md Isa, Nurun Nadhirah; Nawi, Liliwirianis; Musa, Nor Lailatul Wahidah; Mohd Zin, Khairunnisa; Fariha, Nuraina (Universiti Teknologi MARA Cawangan Pahang, 2020)
Apoidea and some species of Diptera play a crucial role in the pollination of plants, honey production and also important in the biological control of agricultural pests. However, due to habitat destruction and lack of knowledge on the importance of bees and flies to human have caused these populations to dwindle. Absence of pollinator agents can lead to significant yield decline and eventually increasing food prices. This study aims to determine and to compare the diversity and the abundance of Apoidea and Diptera in UiTM Pahang. Bees and flies were caught in four different areas using sweep net and bottle traps filled with pheromones. The samples were then sorted, preserved, mounted, dried and identified. Two families of Apoidea (Apidae and Halictidae) and three families of Diptera (Tephritidae, Sarcophagidae and Syrphidae) were found. Fruit plantation has the highest diversity of Apoidea (H = 0.76) while agrotechnology site has the highest diversity of Diptera (H = 0.26). The result obtained was influenced by human activities, weather, captured time and method used. Future studies should focus on proper trap used based on different taxa, enlarging sampling site and extending sample collection time for a more accurate result. The role of Apoidea and Diptera as pollinators for economic contribution should be the main reason to conserve these species and adequately manage their habitat in the future.